Writing PISA-Like Mathematics Items: The Case of Tertiary Mathematics Instructors from a State University in the Philippines - Garcia, Mark Lester B (Archīum Ateneo, 2024)
Mathematics test items in International Large-Scale Assessments (ILSAs) such as the Programme of International Student Assessment (PISA) and the Trends in International Mathematics and Science Study (TIMSS) are nested in contexts defined in their assessment framework (e.g., the Personal, Occupational, Societal, and Scientific contexts in PISA). This study followed the item-writing activities of four tertiary mathematics instructors in the Philippines as they constructed context-based mathematics items. They were tasked to write four items each, following a set of specifications for PISA content and context categories. The data consisted of transcripts from the focus-group discussion which was conducted days after the task. The transcripts were then analyzed using thematic analysis. The results of this study showed that the phenomenon of item-writing in the context of writing PISA-like mathematics items had two themes: the phases of item-writing and the dimensions of item-writing. Findings showed that the respondents struggled to find realistic contexts and that they engaged in a problem-solving task likened to solving a puzzle as they attempted to satisfy the content, context, and process categories in the table of specifications (TOS). This study contributes to filling in the research gap on item-writing activities, particularly those of mathematics teachers in the Philippines- a country whose recent mathematical performance in the PISA 2018, TIMSS 2019, and PISA 2022 was nothing short of dismal.